Taxonomic Reevaluation of the Polylepis sericea Complex (Rosaceae), with the Description of a New Species - Espinoza T.E.B. (2019)
This work would not have been possible without the work of all the plant collectors and herbarium curators (AAU, COL, CUZ, F, GOET, MERF, MO, NY, US, USM, VEN, and Z/ZH) who made specimens (physical or digital) available for study. We thank Katya Romoleroux and one anonymous reviewer who have improved the manuscript with their suggestions and helpful comments. HRQM thanks Vladimir Camel, Wendy Navarro, and Fressia Ames for their support during field work. We thank the Servicio Nacional Forestal y de Fauna Silvestre for providing research authorizations under the R.D.G. No 233-2015, No 237-2015, No 037-2017-SERFOR/DGGSPFFS. TEBEs work was funded by FONDECYTCONCYTEC (No227-2014-FONDECYT). HRQMs work was possible thanks to grant CONCYTEC, Project 149-2015-FONDECYT-DE.